Collaborative learning with augmented reality techniques as a teaching strategy for teaching iterative structures in computer programming fundamentals - Jiménez Toledo, Javier A.; Hurtado, Julio A.; Collazos, Cesar A.; Pantoja Yépez, Libardo (I+ T+ C- Research, Technology and Science, 2014)
This paper presents the experience of validating a model supported collaborative learning with augmented reality techniques as a teaching strategy for teaching students the cyclic structures of first programming fundamentals courses in institutions of higher education modality. The proposed research design evaluated the experimental treatment based on collaborative learning, the results generated interesting indicators of academic achievement with high expectations for student learning.